Molecular mechanism of Be2+-ion binding to HLA-DP2: tetrahedral coordination, conformational changes and multi-ion binding. Issue 2 (13th December 2019) - De, Susmita; Sabu, Gopika; Zacharias, Martin
Abstract : Be small and positive: the smaller size and higher charge of the Be 2+ -ion results in strong binding between the M2 peptide and the β-chain of HLA-DP2, which induces conformational changes at the periphery suitable for TCR binding. Abstract : The chemistry of beryllium is rather unusual, however, less explored as compared to other main group elements. This is mainly attributed to the high toxicity of beryllium, leading to chronic granulomatous pneumonitis, called chronic beryllium disease (CBD). It has been reported that Be 2+ -ion binding to the human leukocyte antigen protein (HLA-DP2) and peptide (M2) results in favorable interaction with the T-cell receptor protein (TCR), which initiates immune-mediated toxicity. We have carried out molecular dynamics (MD) simulations combined with quantum mechanical/molecular mechanical (QM/MM) studies to explore the binding nature of Be 2+ with a HLA-DP2 protein and M2 peptide. The interaction between the negatively charged M2 peptide and the negatively charged binding cleft of HLA-DP2 is unfavorable. However, this interaction is stabilized by one Be 2+ and two Na + -ions bridged by negatively charged carboxyl groups of glutamate residues (β26E and β69E) of the β-chain of HLA-DP2 and one glutamate (p7E) and one aspartate residue (p4D) of the M2 peptide. This multi-ion cavity consists of tetrahedrally coordinated static Be 2+ and Na + -ions, as well as one dynamically exchangeable Na + -ion. The smaller size and higher charge of the Be 2+ -ion as compared to the Na + -ion reduce the distance between the M2 peptide and the β-chain of HLA-DP2, which results in conformational change suitable for TCR binding. However, the replacement of the Be 2+ by the Na + -ion could not generate a suitable binding site for TCR.